Long noncoding RNA ABHD11‐AS1 promote cells proliferation and invasion of colorectal cancer via regulating the miR‐1254‐WNT11 pathway. Issue 7 (7th December 2018) - He, Dedong; Yue, Zhongyi; Liu, Lingling; Fang, Xiangjie; Chen, Liping; Han, Huanhuan
Abstract: The purpose of our study was to investigate the effects of the long noncoding RNA (lncRNA) ABHD11‐AS1 on colorectal cancer (CRC) progression and further explore its possible underlying mechanisms. In the study, we found that ABHD11‐AS1 was highly expressed in CRC tissues and cell lines. High ABHD11‐AS1 expression was correlated with poor overall survival of patients with CRC. ABHD11‐AS1 knockdown reduced CRC cell proliferation, in vitro invasion, and in vivo tumor growth. Investigation of the underlying mechanism showed that ABHD11‐AS1 could act as a molecular sponge of miR‐1254, and WNT11 was a downstream target of miR‐1254 in CRC. Moreover, there was a negative association between ABHD11‐AS1 expression (or WNT11) and miR‐1254 in CRC tissues. The rescue assays showed that WNT11 overexpression partially rescued the effects of ABHD11‐AS1 inhibition on CRC progression. Thus, we demonstrated that ABHD11‐AS1 promotes CRC progression through the miR‐1254‐WNT11 pathway, which provides a new insight into the therapeutic strategies for CRC. Abstract : We demonstrated that the long noncoding RNA (lncRNA) ABHD11‐AS1 promotes colorectal cancer (CRC) progression through the miR‐1254‐WNT11 pathway, which provides a new insight into the therapeutic strategies for CRC.